Gestão de resíduos sólidos urbanos na Região de Integração de Carajás, Pará: desafios e perspectivas - Sidnei Cerqueira dos Santos; Jorge Madeira Nogueira; Thanabi Bellenzier Calderan; Ana Cristina Viana Campos; Rafael Gonçalves Gumiero; Ulisses Brigatto Albino (Confins)
The integrated management of urban solid waste - MSW requires identifying and combining alternatives for collecting, separating and disposing of waste that are, in general, heterogeneous. This heterogeneity manifests itself in different types of waste, which present risks to the environment and living beings, requiring different management alternatives. For this reason, public consortia for solid waste management have received prominence since the promulgation of the National Solid Waste Policy. These consortia enhance the scale of collection, separation, use and final disposal of MSW, with a simultaneous reduction in costs of the entire process. In this context, this work evaluated the challenges and potential of the public consortium for the management of urban solid waste, focusing on the Carajás Integration Region - RIC, Pará. The qualitative approach adopted was based on a broad review of scientific literature, addressing the panorama of public consortia as an integrated solid waste management tool, with an emphasis on the effectiveness of this management model for RIC. The critical assessment of the literature was complemented with technical reports from public consortium observatories and by consultations on official public websites. The results obtained are relevant to support urban and regional planning, aiming at the implementation of an intermunicipal public consortium for solid waste management in RIC.